The effect of stratification and treatment with GA3 in some vegetative and root growth characters of apricot (Prunus armeniaca L.) - علي, علاء عباس (Journal of Kerbala for Agricultural Sciences, 2015)
The experiment was conducted at the college of Agriculture / University of Karbala for the season 2009-2010 on the local apricot seeds to show the effect of periods stratification as well as treatment with Gibberellic acid on seed germination and growth where they were setting seed intervals (0, 30.45 and 60 day) at temperature (5 ± 1 ºC) after that it has been treated with concentrations (0,50 and 100 mg.ltr -1) of Gibberellic acid The results of the statistical analysis showed that the stratification period (60 days) was the best in the average number of( leaves , root length and weight of the wet roots) reaching (18.10, 16.79 cm and 0.562 g) sequentially while the transaction led Gibberellic acid concentration (100 mg.ltr -1) to give the highest in the Each of wet leaves weight , root length and number of leaves as it was (1.747 g, 16.40 cm and 18.44) sequentially while given treatment Gibberellic acid concentration (50 mg.ltr -1) the highest rate in (dry leaves weight, number of roots, the weight of the roots wet and dry) it was (0.588 g, 38.50, 0.578 g and 0.219 g) sequentially. It was not significant the interaction between the periods stratification and treatment with Gibberellic acid concentrations in most of the studied characters except average number of leaves in the transaction (60 day concentration of 100 mg.ltr -1), which was significantly outperformed the rest of the transactions giving it the highest rate of 19.58.